2022
DOI: 10.1002/cam4.5244
|View full text |Cite
|
Sign up to set email alerts
|

Financial toxicity of patients with lung cancer in China: Results from a National Survey Study

Abstract: Financial toxicity (FT) refers to the subjective financial distress and objective financial burden of medical care expenditures. 1 An increasing amount of attention has been paid to FT in patients with cancer, in large part due to the rising costs of cancer diagnosis and treatment. 2 Previous studies of FT in cancer patients have examined the prevalence of FT among subgroups of patients with different cancer types, 3-6 cancer stages, 5,7,8 treatment schemes, 5,9 healthcare coverage systems, [10][11][12] or oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 46 publications
2
10
0
Order By: Relevance
“…Moreover, the average out‐of‐pocket costs for our patients exceeded those of patients diagnosed with breast ($1823), colorectal ($1193), and lung cancer ($1649) 29 . In comparison to patients receiving cancer treatment, the HS population demonstrates FT levels similar to patients with breast, lung, and colorectal cancer 30–36 . While these comparisons do not deem HS a more burdensome disease or requiring more extensive health care coverage than any malignancy, they allude to the notion that the indirect costs of HS may be greater than what is perceived by the health care system.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Moreover, the average out‐of‐pocket costs for our patients exceeded those of patients diagnosed with breast ($1823), colorectal ($1193), and lung cancer ($1649) 29 . In comparison to patients receiving cancer treatment, the HS population demonstrates FT levels similar to patients with breast, lung, and colorectal cancer 30–36 . While these comparisons do not deem HS a more burdensome disease or requiring more extensive health care coverage than any malignancy, they allude to the notion that the indirect costs of HS may be greater than what is perceived by the health care system.…”
Section: Discussionmentioning
confidence: 87%
“…29 In comparison to patients receiving cancer treatment, the HS population demonstrates FT levels similar to patients with breast, lung, and colorectal cancer. [30][31][32][33][34][35][36]…”
Section: Insurance and Financial Factorsmentioning
confidence: 99%
“…The incidence of lung cancer has risen over the past decade, 3 increasing the physical, psychological, and economic strain on patients. Hospitalization costs constitute a significant part of the overall medical expenses for cancer in China 4–7 . This financial strain, often compounded by a loss of income, can adversely affect patients, resulting depression, and diminished sense of financial well‐being.…”
Section: Introductionmentioning
confidence: 99%
“…Hospitalization costs constitute a significant part of the overall medical expenses for cancer in China. [4][5][6][7] This financial strain, often compounded by a loss of income, can adversely affect patients, resulting depression, and diminished sense of financial well-being. Zafar et al introduced the term "financial toxicity" to describe these adverse impacts.…”
Section: Introductionmentioning
confidence: 99%
“…FT adversely affects patients' preferences for decision making, adherence toward treatment and drugs, and rehabilitation during follow-up care, resulting in a decreasing life quality [16][17][18]. Results from a national survey study in China showed that 77% of the lung cancer patients had a presence of FT [19]. Immunotherapy is among the most expensive of the new treatments coming forth from cancer research [17,20].…”
Section: Introductionmentioning
confidence: 99%